Investigation of the formation of Copper(II)-tryptophane-aspirin ternary complexes - (:unkn) unknown (Chemical Publishing Co., 2010)
Formation constants and the stoichiometric composition of the potentially therapeutic complex of Cu-tryptophane-aspirin were determined potentiometrically, at 25 °C (± 1) and I = 0.11. The formation constants of binary Cu(II)-aspirin (1:2) complex, on which few and many information exist in literature, were also investigated. Distribution of species was calculated for various pH values. Cu(II)-Tryptophan-aspirin ternary complex formation was confirmed through UV and IR spectrometry and qualitative metal analysis in the precipitates. The stability constants of ternary complexes of Cu(II)-Tryp-ASA were reported, which is important for further studies on this therapeutically important ternary complex, both from the point of synthesis and commenting on its pharmacokinetics.
Keywords: Aspirin; Copper ternary complex; Spectroscopy; Stability constant; Tryptophane